Association of Metabolic Syndrome With Prevalence of Obstructive Sleep Apnea and Remission After Sleeve Gastrectomy - Chen, Yufei; Chen, Lijia; Ye, Lingxia; Jin, Jiabin; Sun, Yingkai; Zhang, Ling; Zhao, Shaoqian; Zhang, Yifei; Wang, Weiqing; Gu, Weiqiong; Hong, Jie (Frontiers in Physiology, 2021)
Obesity is an important risk factor for metabolic syndrome and obstructive sleep apnea (OSA). Bariatric surgery has been shown to effectively reduce weight and obesity-related comorbidities. However, the prevalence and severity of OSA in obese patients with different baseline metabolic states and the improvements of OSA after bariatric surgery remain unknown. The main aims of this study were to ascertain the prevalence of OSA in young Chinese obese patients with different metabolic states and to evaluate their respective OSA remission after laparoscopic sleeve gastrectomy. We first performed a cross-sectional study involving 123 metabolically healthy obese patients and 200 metabolically unhealthy obese patients (who had the same age and BMI ranges) to estimate the prevalence of OSA at baseline. Then we performed a retrospective study, which was registered at ClinicalTrials.gov (ref. NCT02653430) of 67 patients who underwent laparoscopic sleeve gastrectomy to evaluate the remission of OSA. Metabolically healthy and unhealthy obese patients had similar apnea-hypopnea index levels (16.6±22.0 vs 16.7±18.7 events/h, P=0.512) and prevalence of OSA (66.7% vs 69.0%, P=0.662). Male sex, age, waist circumference and lower liver-to-spleen ratio were independent risk factors for OSA. After laparoscopic sleeve gastrectomy, no difference was found in the decrease in body mass index change (10.8±4.8 vs 10.8±3.0 kg/m2, P=0.996) or the decrease in the apnea-hypopnea index (18.9±24.6 vs 17.0±24.0 events/h, P=0.800). The remission of moderate-to-severe OSA was observed in the MHO (36.3%; 54.5% to 18.2%, P=0.125) and MUO (32.2%; 66.1% to 33.9%, P=0.001) patients. These results suggest that, in patients with obesity, metabolic syndrome does not add extra risk for the prevalence or severity of OSA. Both metabolically healthy and unhealthy obese patients could benefit equally from laparoscopic sleeve gastrectomy in terms of weight loss and obstructive sleep apnea remission.